Meta-Analisis Efektivitas Pembelajaran Berdiferensiasi Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA - I G. A. A. Dyah Armayanti; I Wayan Redhana; I Nyoman Tika (Postgraduate, University of Mataram, 2025)
The diversity of student learning styles is one of the internal factors that influences student learning outcomes. Differentiated instruction is a learning approach that emphasizes learning methods adapted to student’s diversity. This study aims to examine the impact of differentiated instruction on student’s learning outcomes in science education. This study is a meta-analysis that reviewed 10 articles Article were collected by Publish or Perish software with Crosseff as the database and the article selection used PRISMA. Data were analyzed according to the meta-analysis method, including the research bias test, effect size calculation of each article, heterogeneity test, and point estimation test. The result showed that the differentiated instruction in science learning gives a large effect on student’s learning outcomes by the value of the effect size is 1,136. It means that the differentiated instruction learning has a significant and large effect on student learning outcomes in science learning. Based on this study, the differentiated instruction can be used as a recommendation for teachers to implement in order to improve student’s learning outcomes. In addition, this study also expected to inspire other research to examine the characteristics of each other article to determine the factors that influence the result of differences in effect size of each article.